Rose aromatherapy as a complementary approach to reduce labor pain in the first stage of active labor: - Nuari, Jen Astika; Hidayanti, Desi; Sariaty, Saur (Poltekkes Kemenkes Yogyakarta, 2024)
Labor pain is a significant physiological and psychological stressor for women in childbirth. If unmanaged, it may lead to adverse maternal and fetal outcomes. Non-pharmacological methods such as aromatherapy offer a low-risk alternative for pain management. Rose aromatherapy, with its known relaxing and antispasmodic properties, has been proposed to reduce labor pain through inhalation. This study aimed to examine the effect of rose aromatherapy on labor pain during the first stage of active labor. This pre-experimental study used a one-group pretest-posttest design involving 36 laboring mothers in the active phase I at Garuda Public Health Center, Bandung, Indonesia. Participants received rose aromatherapy via inhalation for 10 minutes. Labor pain was measured before and after the intervention using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon signed-rank test. The mean labor pain score decreased from 8.58 (SD = 0.94) before the intervention to 7.25 (SD = 1.38) after, with a statistically significant difference (Z = -5.15, p < 0.001). Rose aromatherapy significantly reduces labor pain during the first active phase of labor. These findings support its use as a complementary intervention in midwifery care to enhance maternal comfort during childbirth.